Peningkatan Derajat Kesehatan Melalui Kegiatan Observasi Psikologi Perkembangan Anak dengan Metode Terapi Bermain - Desi Natalia Trijayanti Idris; Srinalesti Mahanani; Aries Wahyuningsih (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Early childhood is a child who is in the process of growth and development. At this age all aspects of child development progress very rapidly. Aspects of development in early childhood include intellectual, physical-motor, socio-emotional, language, moral and religious aspects. All aspects of development that exist in this child should be the concern of educators so that these aspects of development can develop optimally. The purpose of this community service activity is to observe the developmental psychology of children aged 3-5 years at Tunas Bangsa Kindergarten, Kediri City. The approach offered for increasing the degree of health through observation of child development psychology with the play therapy method is the method of observation and puppet stage play therapy. The results of this community service activity The number of children who took part in developmental psychological observation activities and play therapy through the puppet stage were 29 children consisting of 19 girls (65.52) and 10 boys (34.48). The psychological level of child development was obtained from 29 children, 23 children had good developmental psychology and 6 children had poor developmental psychology. It is hoped that the play therapy method with the puppet stage will improve the psychology of child development so that children can achieve maximum growth and development according to their age.